Image Transforms:
5a/06/11. Using Fast Hadamard transform, find X ([n] for x (n) ={4, 2, 2, 4}
1g/12/10. Prove that 2Dimensional DFT matrix is unitary matrix
4c/12/10. Derive Fast Walsh Transform flow graph for N=4
3a/12/10. Let x (n) = { 2 [ n] + 3 [ n ] + 4 [ n 2] + 5 [ n 3]
Find 4 point DFT using FFT flow graph
2c/12/10. Given f (x , y ) =
5 6 7h (x, y) =
8 9 `10
1 2
3 4
p [ n ] = ( 1)n x [ n ]
( 2)
q [ n ] = x [ n +1]
2
x is a N . 1 vector
T is a N . N matrix
Then yi
= ti j . X j
Y =
y0 t00 t01 .
y1
.
=
.
yn1
tn10
i 0, 1, 2, . . . , N1
T
. x
. T0 n1 x0 (y0 = t00 x0 + t01. x1 +
t10 t11 .
.
.
N rows, 1 column
. . .
. . .
. . .
rows
..
+ t0n1xn1)
t1 n1 x1
.
.
tn1 n1
x
xn1
1
If T is a unitary matrix, then
T* =T
(conjugate transpose
matrix inverse)
T* indicate complex conjugate of matrix T (imaginary part negated)
i, j rowsj,as
i columns or columns as rows
A indicate transpose of a matrix A, write
1 transpose of matrix A = A
1
I identity matrix =
Symmetric matrix:
If transpose of matrix is equal to the Matrix
QT = Q
orthogonal matrix:
The matrix whose column and rows are
orthogonal unit vectors
or whose transpose is equal to its inverse
QT = Q 1
y matrix
T is unitary matrix, Then
T*
=T
ut T . T
=I
1
where I
1
1
T . T* = T . T
is identity matrix
* = I , identity matrix
(Matrix T multiplied by conjugate, transpose of matrix T = Identity m
T. T
1
T*
1
T =
=I
=T
T . T = T . T
= I identity m
W
.
W*
1 1 1 1
1 j 1 j
1 1 1 1
1 j 1 j
1
.
1
1
1 1 1
1 j 1 j
1 1 1
j 1 j
4 0 00
=
0 4 0 0
0 0 4 0
0 0 0 4
= 4[I]
n
0
m
0 [ ]I, k
1 [ ]i, k
.
.
m = N1
]I, k .
. [
]I, k
]i, k .
.
. [
]i, k
N xN submatrices
n =N1
.
[
]i, k
]i,k .
]i,k
Tcol (k, n)
N1
Fm, n =
T (i, m)
i =0
k =0
F= TfT
Here Transformation T is both separable and symmetric
The DFT matrix is both symmetric a well as separable
hence Transform can be obtained by using:
F = T. f. T
This is standard formula for computing
transform
of a 2D signal
11
4 8 12 8
2 2 2 2
0 0 0 0
2 2 2 2
32
8
0
8
8
0
0
0
0 8
0 0
0 0
0 0
T is symmetric
1 1 1 1
x 1 j 1 j
1 1 1 1
1 j 1 j
12
n. k
0 k N1
(twiddle factor)
=  W N Symmetric
WN
k+N
WN = W N
Periodic
These ktwo properties
j 2 k/ N reduce the number of computations
WN = e
k + N/2 j 2 k/ N
 j2 N / 2N
j 2 k/ N
j
k
k
=
W
.
1
=
W
N
N
WN
=e
. e
=e
.e
k
WN k + N = vvN e j2 ( k+ N)/ N = WN e j2 k/N . W Ne j2 = W14
N
N1
X [k] =
n. k
x (n) WN
n =0
Where WN = e j 2 / N
k = 0, 1, 2, . . . N1
Decimationintime: splits
and even parts:
n. k the input x (n) into
n. odd
k
X [k] = x (n) WN
n even (0, 2, 4. )
x (n) WN
n odd (1, 3, 5
N/2 1
X [k] =
n=0
N/2 1
x (2n) WN2 n.k +
n=02n. k
N/2 1
X2[k] =
n=0
N/2 1
x (2n) WN +
n=0
Now WN
= WN/2
2nk
x (2n+1) WN(2n+1). k
2n. k
WN = e
jx2.(2n+1)
2 / N WN j 2 . /W
(NN/2)
=e
15
=WN/2
N/2 1
X [k] =
n=0
n. k
x (2n) WN/2
N/2 1
k
+
WN.
n=0
N/2 1
nk
Let F1(k) = x (2n) WN/2
n=0
X (k) =
k
F1(k) + WN
X (k) =
F2(k)
Both are
n.k
x (2n+1) WN/2
DFTs
N/2 1
F2(k) =
x(2n+1) WN/2
n=0
N/2 point
nk
F1(k) + WN . F2(k)
for k = 0, 1, 2. .
16
N/2 1
F1(k+N/2) = F1(k)
and
F2(k+N/2) = F2(k)
WN (k+N/2) =  W Nk
We get
k = 0, 1, 2 . . .
X( k + N/2) =
F1(k)  WN
F2(k)
multiplying w
2
2 . (N/2)
+ 2.N/2
17
X (k )
X(k+ N/2) =
(1)
for k = 0 to N/2 1
For k = 1
X ( 4 ) = F1(0 ) W4 0 . F2 (0)
from (2)
X ( 5 ) = F1(1 ) W4 1 . F2 (1)
For k = 2
For k = 3
from (1)
For k = 1
For k = 2
= 0 to 3
For k = 0
X ( 6 ) = F1(2 ) W4 2 . F2 (2)
For k = 3
(2)
X ( 7 ) = F1(3 ) W4 3 . F2 (3)
18
The equations (1) and (2) can be shown using a signal flow graph
for N= 8 as follows:
Input split
Even/odd
F1(0)
F1(0) + WN0 F2(0)
x(0) X[0]
N/2 point
WN 0
F1(1)
F1(1) + WN1 F2(1)
x(2) DFT
X[1]
(For N =8
WN1
2
F1(2)
x(4) 4 point
X[2]F1(2) + WN F2(2)
DFT)
WFN2(3) + W 3 F (3)
F1(3)
1
N
2
x(6) X[3]
WN3
x(1) N/2 point
DFT
x(3) (For N=8
4 point
DFT) x(5) x(7) 
F2(0)
F2(1)
F2(2)
F2(3)
WN0
F1(0)  WN0 F2(0)
X[4]
WNF11(1) WN1 F2(1)
X[5]
2
WNF
2
1(2) WN F2(2)
X[6]
3
WNF (3) W 3 F (3)
1
N
2
X[7]
19
X (k )
= F1 (k) + W Nk F2(k)
X(k+ N/2) =
F1(k) W Nk . F2(k)
(1)
for k = 0 to N/2 1
(2)
G1(k)
F1(k+N/4) =
F2(k) =
G1(k)
H1(k)
F2(k+N/4) =
+ WN/2k G2(k)

WN/2k G2(k)
+ WN/2k H2(k)
H1(k) 
WN/2k H2(k)
0 to 1
(N/4 1)
20
G1(0)
x(0) 
F1(0)
WN/2
N/4
G (1)
F1(1)
Point x(4)  1
WN/21
DFT
G2(0)
WN/20F1(2)
N/4
x(3) Point
DFT
x(7) 
H1(0)
H1(1)
F2(0)
WN/20
F2(1)
WN/21
H2(0)
1
WN/2F
2(2)
X[0]
X[1]
WN0
WN1
X[2]
X[3]
X[4]
X[5]
X[6]
X[7]
21
WN2
WN3
WN0
WN1
WN2
WN3
+1
1
Hence the final flow graph is shown as following
22
x(0)
1 x (4)
x (2)
1
x (6)
x (1)
1
x (5)
x (3)
1
x (7)
G1(0)
G1(1)
F1(0)
WN/2
F1(1)
WN/21
G2(0)
G2(1)
WN/21 F1(3)
H2(0)
F2(0)
WN/20
WN/21
X[1]
WN0
WN1
WN/2F0 1(2)
H1(0)
H1(1)
X[0]
F2(1)
0
WN/2F
2(2)
X[2]
X[3]
WN2
WN3
X[4]
X[5]
X[6]
X[7]
WN0
WN1
WN2
WN3
Bitreversal
The order of input data can be obtained by reversing bits of
binary representation
000
001
010
011
000
100
010
110
x(0)
x(4)
x(2)
x(6)
100
101
110
111
001
101
011
111
x(1)
x(5)
x(3)
x(7)
24
K = 0, 1, 2, . . . N1
N/2 1
X [k] =
n=0
N/2 1
x (n) WNnk +
n=0
K = 0, 1, . . (N/2  1)
(1)
and
g1(n) WN/2 nk
g2(n) WN/2 nk
(3)
(4)
For n =0
g1(0) = x (0) + x (4)
g2(0) = x (0)  x (4)
x(0)
x(1)
x(2)
g1(3)
x(3)
(4 point
DFT)
X[0]
X[2]
X[4]
X[6)]
X(0)  x(4)
wN0 g2(0)
x(4)
1
x(5)
1
x(6)
x(7)
1
1
wN1
wN2
wN3
N/2 Point
g2(1) DFT
g2(2)
(4 point
g2(3) DFT)
X[1]
X[3)
X[5]
X[7]
from (3)
k = 0, 1, . . (N/4 1)
29
from (4)
x(0)
x(1)
x(2)
1
x(3)
1
1
x(5)
x(6)
1
1
X(4)
wN/20
1
x(4)
x(7)
X(2)
1
wN/21
1
X(6)
wN0
X(1)
wN1
wN2
wN3
X(3)
X(5)
1
1
1
wN/20
wN/21
X(7)
1
30
1
2
3
2
2
3
4
3
1
2
3
2
f(0)
f(2)
1
1
f(1)
f(3)
W
G(1)
1
H(0)
1
H(1)
First Row {f(0), f(1), f(2), f(3)} = {0, 1, 2, 1}
G(0) = f(0) + f(2) = 0 + 2 = 2
G(1) = f(0)  f(2) = 0  2 = 2
H(0) = f(1) + f(3) = 1 + 1 = 2
H(1) = f(1)  f(3) = 1  1 = 0
0
4
W 41
 W 40
 W 41
X[0]
X[1]
X[2]
X[3]
WN = e j2
/N
WNnk = W4 nk = e j2
32
. 0. 0
=1
{4 8 12 8}
f(0) = 4,
f(1) = 8,
32 8 0 8
FFT of 1st column
0
FFT of 2nd column
0
FFT of 3rd column
0
FFT of 4th column
33
0 x N1
Where
(0) = 1/N;
(u) = 2/N
for u = 0
for 1 u N1
34
0 x N1
D DCT pair:
N1 N1
u, v) = (u). (v)
f (x, y ) cos [ (2x +1).u / 2N] . cos [ (2y +1).v / 2
x =0 y =0
For
u, v = 0, 1, 2, . . , N1
35
u =0,
. Cos [ (2v +1). u / 2N]
0 v N1
1 u N1,
0 v N1
36
C = C*
C1 = C
C. C
(From T.T * = I
=I
identity matrix
(DFT F =T f)
(DFT F = T f T)
37
0 v N1
1 u N1,
0 v N1
C will be N x N = 4x 4 matrix
u v 0
1
2
3
0 0.5 0.5 0.5 0.5
1 0.653
0.2705 0.2705 0.653
2 0.5 0.5 0.5 0.5
3 0.2705 0.653 0.635 0.2705
C is not symmetric
1/N
for (u=0, v=0 to N1) =
= = 0.5
2/N . Cos [ (2v +1). u / 2N] for (u=1, v=0) = 2/4 . cos /8 = 0.635
for (u=2, v=0) = 2/4 .cos / 4 = 0.5
38
F=C.f
C
f = { 1, 2, 4, 7}
f
F
1 7
0.2705
0.653
. 2 = 4.459
4 1
0.635 0.2705
7 0.3170
2 4 4 2
C (Transpose)
2 4 4 2
0.5 0.653 0.5
0.653 . 4 6 8 3 . 0.5
2 8 10 4
0.5 0.2705 0.5
0.2705
3 8 6 2
0.5
0.653
2.3087 0.8957
1.5 1.6885
0.9562 0.2448
0.2705
0.2705 0.5 0.653
0.635
0.653 0.5  0.2705
39
W=
2
1x
1
2
3x
A x B =1
5
3
5
3
a12B . . a1nB
a22B . . a2nB
.
.
.
an2B If. Aann
=B
22 x 5
1 3
25 x5
1 3=
1
3
2
5
2 5
1 3
B=
2 5
1 3
6 15
3 9
4 10
2 6
10 25
5 15
40
amard Transform
1 1
1 1
also written as
+ +
+ 
1
column
1
1
1
[1
The
1
11
1
second1column
1
1
41
A =
x1 1
1 1
1 1
(A transpose: row to col.)
1 1
2 =02 x
1= 2
0[I]
0 2
0 1
1/2
1 1
1 1
42
1/2 1/2
A. A =
1/2 1/2
A = 1/2
1/2 1/2
=
1/2 1/2
1 1
1 1
= [I]
Therefore
1 1
HN(2) = 1/2
1 1
is called normalized 2x 2 Hadamard matrix
43
1 0
0 1
1 =
. 1H(2)
1 1
1 1
1 1
H(4) =
1 1
1 1
1 1
1 1
1  1
 1 +1
1. [H(2) 1. [H(2)
1. [H(2) 1. [H(2)
Sign changes
0
3
1
2
= 4[I]
4x
0 1 0 0
0 0 1 0
0 0 0 1
1 0 0 0
44
1
=
1 1 1
1 1 1 1
1 1 1 1
1 1 1
A =
1 1 1 1
1 1 1 1
Check A . A = 1
1 1 1 1
1 1 1 1 1 1 1
1 .
1 1 1 1
1 1 1 1 0 0 4
1 1 1 1
0
4 0 0 0
=
0 4 0 0
0
0 0 4
45
= 4[I]
8 = 23
1. [H(4)]
( Kronecker product)
1. [H(4)]
Sign change
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
H(8) =
1 1 1 1
1 1 1 1
1 11 1
1 1 1 1
1 1 1 10
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
7
3
4
1
6
2
5
46
Using equation:
A. A
=[I]
Thus H(8)N = 1 8
normalized
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
Sign
change
0
7
3
4
1 1 1 1 1 1 1 1 1
1 1 1 1 1 1 1 1 6
1 1 1 1 1 1 1 1 2
1 1 1can 1be
1considered
1 1 5 to be samples of rectangular
The rows of Hadamard1 matrix
waves with subperiod of 1/ N units
47
Dotted lines
are the
Fourier basis
48
X=T.x
X [n] = [ H (N). x (n)]
49
12th August
50
X[n] =
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
H (N)
1
2
0
3
x (n)
1 +2 +0 +3
1 2 +0 3
1 + 2 0 3
1 2 0 +3
6
4
0
2
X [n]
51
x(n) = 1/4
1/ N
1 1 1 1
1 1 1 1 .
1 1 1 1
1 1 1 1
H(N)
6
4 = 1/4
0
2
6 4 +0 +2
6 +4 +0 2
6 4 0 2
6 +4 0 2
= 1/4
X [n]
52
4
8
0
12
1
2
0
3
F = T. f . T = [ H (N) . f. H (N)]
1 1 1 1
1 1 1 1
34 2 6 6
2 2 2 2
2121
53
X [n] =
4
2
2
4
12
0
0
4
3 per row
54
x(0)
x(1)
= 1 1
= 1 1
x(0)
.
x(1)
1
x(0)  x(1)
X [0]
X[ 1 ]
X(1). ()
2 point Butterfly for Haddamard
55
1 1
1 1
x(0)
1 1
1 1
x(2)
x(3)
x(1)
H(2)
=
H(2)
x(0)
x(1)
H(2)  H(2)
x(2)
x(3)
56
=1 1
1 1
x(0)
x(1)
H(0) =[H(2)]
x(2)
H(1)
x(3)
From above:
G(0) = x(0 )+ x(1)
G(1) = x(0)  x(1)
4 additions
H(0) = x(2) + x(3)
H(1) = x(2)  x(3)
Writing X [. ] in terms of G (.) and H(.)
X(0) = [ G(0) + H(0) ]
[ { x(0) + x(1)} + {x(2) +x(3)}]
X(1) = [ G(1) + H(1) ]
[ { x(0)  x(1)} + {x(2) x(3)}]
4 additions
X(2) = [ G(0)  H(0) ]
[ { x(0) + x(1)}  {x(2) +x(3)}]
X(3) = [ G(1)  H(1) ]
[ { x(0)  x(1)}  {x(2) x(3)}]
57
x(0)
x(1)
X [0]
G (1)
= x(0 ) x(1)
H (0)
= x(2 )+ x(3)
1
x(2)
x(3)
= G(0 )+ H(0)
G (0)
X [1]
= x(2 ) x(3)
H (1)
1
X [2]
1
X [3]
1
= G(1 )+ H(1)
= G(0 )H(0)
= G(1 )H(1)
58
Given x (n) { 4, 2, 2 4}
Find X [n] using Fast Hadamard Transform
Since N = 4, a 4point butterfly diagram can be used
G (0) = 6
x(0) 4
x(1) 2
G (1) = 2
1
x(2) 2
x(3) 4
X [0] = 12
X [1] = 0
H (0) = 6
1
H (1) = 2
1
1
X [2] = 0
X [3] = 4
= 6 + 6 = 12
= 2 + 2 = 0
= 6+ 6 = 0
= 2  2 = 4
59
For N =8
X[0]
X[1]
X[2]
X[3]
X[4]
X[5]
X[6]
X[7]
X[0]
X[1]
X[2]
F
X[3]
X[4]
K
X[5]
X[6]
H
X[7]
E
H(4)
H(4)
x(0)
H(4)
x(2)
x(3)
x(4)
 H(4)
x(6)
x(7)
H(2)
H(2)
H(2)
H(2)
H(2)
H(2)
H(2)
 H(2)
H(2)
x(1)
H(2)
x(3)
H(2)
x(5)
H(2)
x(7)
x(1)
x(5)
H(2)
x(0)
H(2)
x(2)
H(2)
x(4)
H(2)
x(6)
60
Let
E [0] = 1
E [1] = 1 1
1
x (0)
x (1)
F [2] = 1 1
F [3] = 1 1
x (2)
x (3)
G [4] = 1 1
G [5] = 1 1
x (4)
x (5)
H [6] = 1 1
F [7] = 1 1
x (6)
x (7)
E(0)
x(0)
H(4) I(0)
H(8)
X [0]
E(1)
x(1)
1
F(0)
x(2)
I(1)
X [1]
I(2)
X [2]
I(3)
X [3]
J(0)
X [4]
G(1)
x(5)
J(1)
X [5]
H(0)
x(6)
J(2)
X [6]
J(3)
X [7]
F(1)
x(3)
1
G(0)
x(4)
1
H(1)
x(7)
1
1
1
1
1
1
1
1
1
X[0] = I[0] + J[0],
X[1] = I[1] + J[1],
X[2] = I[2] + J[2],
X[3] = I[3] + J[3],
E(0) =3
x(0)
E(1) =1
x(1)
F(0) =2
x(2)
F(1) =0
x(3)
3
2
1
2
H(4) I(0) =5
H(8)
X [0]
=13
I(1) =1
X [1]
=1
I(2) =1
X [2]
=3
I(3) =1
X [3]
=1
G(0) =5
x(4)
J(0)=8
X [4]
G(1) =1
x(5)
J(1)=0
X [5]
H(0) =3
x(6)
J(2)=2
X [6]
J(3)=2
X [7]
H(1) =1
x(7)
1
1
1
1
I(0) = E(0) + F(0), I(2) = E(0)  F(0)
I(1) = E(1) + F(1), I(3) = E(1)  F(1)
3
1
=1
1
=1
1
1
X[0] = I[0] + J[0],
X[1] = I[1] + J[1],
X[2] = I[2] + J[2],
X[7] = I[3] + J[3],
=3
X[4] = I[0] J[0]
X[5] = I[1] J[1]
X[6] = I[2] J[2]
X[7] = I[3] J[3]
63
Walsh Transform:
The Walsh transform matrix is obtained from Hadamard matrix
by rearranging the rows in increasing order of sign
Sign change
H(8) =
W(8) =
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 10
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 11 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 11 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
7
3
4
1
6
2
5
0
1
2
3
4
5
6
7
64
65
Sequency
Sign changes
66
H(4) =
1 1
1 1
1 1
1 1
0
3
1 1
1 1
1  1
 1 +1
1
2
Sign change
1 1
1  1
 1 +1
1 1
0
1
2
3
W (n)
1 1
1 1
1 1
1 1
.
1 1
1  1
 1 +1
1 1
x (n)
..
1
2
0
3
X [n]
1 +2 +0 +3
= 1 +2 0 3
1 2 0 +3
2
1 2 +0 3
4
67
6
=
x [0,1]
log22 = 1
20 =1
q =1
1;
1;
0 x 0.5
0.5 x 1
69
h00(x)
1/2
1/2
0.5
0.5
1/2
1/2
1
1
1/2
1 1
It is same as Hadamard HN(2)
1 1
70
Haar(4) = 1/ 4
Haar(8) for N = 8
Haar(8) = 1/ 8
1
1
2
0
2
0
0
0
1
1
2
0
2
0
0
0
1 1 1
1 1 1
2 2 0
0
0 2
0
0 0
2 2 0
0
0 2
0
0 0
1
1
0
2
0
0
2
0
1
1
1 1
0
0
2 2
0
0
0
0
0
0
2 2
= 1/ 4
1
1 1 1
1
1 1 .1 1 =1/2 2
2 2 0 0
0
0 0 2 2
3
1+2+0+3
1+203 =1/2
2 22+0+0
0+0 +0 32
72
6
0
2
32
F=
1 1 1 1
1 1 1 1
.
2 2 0 0
0 0 2 2
8.5
1.5
0.707
1.414
f.
2
1
2
1
Haar (N)
1 2 1
1 1 1 1
2 3 2
1 1 1 1
. 1/ 4
3 4 3
2 2 0 0
2 32
0 0 2 2
73
Haar (2)M =
1
1 1 1
1 1 1 1
1 1
0 0
Haar(4)M =0 0 1 1
1
1
1
0
1
0
Haar(8) M =0
0
1 1 1 1 1 1 1
1
1 1 1 1 1 1
1
1 1 0 0 0 0
0
0 0 1 1 1 1
1
0 0 0 0 0 0
0
1 1 0 0 0 0
0
0 0 1 1 0 0
0 0 0 0 0 0 1 1
Global properties
SemiGlobal properties
Local properties
74
E(0)
x(0)
E(1)
1 x(1)
G(0)
x(2)
G(1)
1 x(3)
A(0)
X[4]
1
A(1)
B(0)
1
x(5)H(1)
x(6)F(0)
X[2]
X[5]
x(4)H(0)
1
X[0]
1
X[1]
X[6]
B(1)
1
x(7)F(1)
1
X[3]
X[7]
75
10+4 = 14
x(0)
8+28= 10
1
x(1)2
82 = 6
x(2)1
1+3 = 4
1
X[2] 6
104 = 6
1 x(3)
133 = 2
X[5] 2
11+11 = 22
x(4)5+6
5 = 11
1
6 = 1
1 x(5)56
x(6)4+7
4 = 11
X[1]
8 = 8
1422
X[6] 1
1
1111 = 0
X[3] 0
7 = 3
1 x(7)47
X[7] 3
76
1
1
1
0
1
0
0
0
1 1 1 1
1
1 1 1
1
1 1 0
0
0 01
1
0 0 0
0
1 1 0
0
0 .0 1
0 0 0 0 0
x(n)
1
1
0
1
0
0
1
0
1
1
0
1
0
0
=0
1
1
1
0
1
0
0
0
1
X
8
2
1
3
5
6
4
7
8+2+1+3+5+6+4+7 = 36
8+2+1+3 5 647 = 8
8+21 3
=6
+5+647 = 0
82+0+0 0 000 = 6
0+0+13 0 000 = 2
0+0+0+0 +5 600 = 1
0+0+0+0 0 0+47 = 3
36
8
6
0
6
2
1
3
77
Col. 0
u/v 1 1 1 1
00
1 1 1 1
1
1 1 1 1
1
1 1 1 1
1
1 1 1 1
1
10
1 1 1 1
1
1 1 1 1
1
11 1 1
1
11 1 1
1
20
1 1 1 1
1
11 1 1
1
1 1 1 1
1
11 1 1
1
1
1 1 1 1
01
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
11
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
21
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
2
3
1 1 1 1
02
03
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
12
13
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
22
23
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1
1 1
1 1
1 1
1 1
1 1
1 1
1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1781
rows
1 1 1
1
1
1
1
1
1
1 1
1
1
1
2 1
1
1
1
3 1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1 1 1 1
1 1 1 1
11 1 1
1 11 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
0
1
1 1 1 1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1
1 1
1 1
1 1
1
1
1
1
1
1
1
1
2
1 1 1
1
1
1
1
1
1
1
1
1
1
1
1
3
1
1
1
1
1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1
1
1
1
1 1
1 1
1 1
1 1
1
1
1
1
1 1 1 1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1 1 1 1
1 1 1 1
1 1 1 1
1 1 1 1
1
1
1
1
1 1
1 1
1 1
1 1
1
1
1
1
1 1 1
1 1 1
1 1 1
1791 1
1
1
1
1
80
81
END
82
WN = e j2
/N
WNnk = W4 nk = e j2
W 40
W41 =  j
W42 = 1
W43 = j
W44 = 1
83
. 0. 0
=1
3a / 12/2010
Let x (n) = { 2 [ n] + 3 [ n 1] + 4 [ n 2] + 5 [ n 3]
Find 4 point DFT using FFT flow graph
From above x (n) = { 2, 3, 4, 5}
x (0)
x (2)
x (1)
x (3)
4
1
2
2
3
51
8
2
8
2
14
X (0)
W 40
2 +2j
X(1)
W 41
2
X(2)
W40
2 2j
X (3)
W41
W40 = 1, W41 =  j
84
85